2007
DOI: 10.1038/sj.emboj.7601734
|View full text |Cite
|
Sign up to set email alerts
|

Individual CREB-target genes dictate usage of distinct cAMP-responsive coactivation mechanisms

Abstract: CREB is a key mediator of cAMP-and calcium-inducible transcription, where phosphorylation of serine 133 in its Kinase-Inducible Domain (KID) is often equated with transactivation. Phospho-Ser133 is required for CREB to bind the KIX domain of the coactivators CBP and p300 (CBP/p300) in vitro, although the importance of this archetype coactivator interaction for endogenous gene expression is unclear. Here, we show that the CREB interaction with KIX is necessary for only a part of cAMPinducible transcription and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
121
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 52 publications
5
121
0
Order By: Relevance
“…In further support of normal Rhokinase activity in the absence of Mdm2, we observed no differences in serine 133 phosphorylation of CREB in p53 À/À and p53 À/À ;mdm2 À/À MEFs upon induction of adipogenesis (Supplementary Figure 7). Although CREB phosphorylation was comparable in MEFs of both genotypes, the induction of several cAMP-responsive CREB target genes 8,30 was perturbed in p53 À/À ;mdm2 À/À MEFs upon IBMX treatment (Figure 4a). We therefore speculated whether Mdm2 could be a direct modulator of CREB activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In further support of normal Rhokinase activity in the absence of Mdm2, we observed no differences in serine 133 phosphorylation of CREB in p53 À/À and p53 À/À ;mdm2 À/À MEFs upon induction of adipogenesis (Supplementary Figure 7). Although CREB phosphorylation was comparable in MEFs of both genotypes, the induction of several cAMP-responsive CREB target genes 8,30 was perturbed in p53 À/À ;mdm2 À/À MEFs upon IBMX treatment (Figure 4a). We therefore speculated whether Mdm2 could be a direct modulator of CREB activity.…”
Section: Resultsmentioning
confidence: 99%
“…The Crtcs solely coactivate CREB bound to genes regulated by cAMP 9 by facilitating the recruitment of the two histone acetylases p300 and CBP to CREB. 8,9 Under basal conditions, Crtc is localized to the cytoplasm as a result of a phosphorylation-dependent interaction with 14-3-3 proteins, mediated by members of the salt-inducible kinase (SIK) family. Upon elevated cAMP levels, PKA inhibits the SIKs, leading to dephosphorylation and translocation of Crtc to the nucleus and subsequent coactivation of CREB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic expression of TORCs bypasses normal regulatory mechanisms and activates reporter genes many hundredfold, suggesting that TORCs either have intrinsic enzymatic activity or recruit catalytic proteins. Recent studies demonstrate that TORC2 mediates target gene activation in response to cAMP in part by cooperative interactions with CBP (14,15); however, CBP/p300 recruitment cannot fully explain how TORCs robustly activate transcription. Moreover, the contribution of each of these coactivators varies, depending on the cAMP-responsive promoter (15).…”
mentioning
confidence: 99%
“…CREB is a critical mediator of cAMP‐ and calcium‐inducible transcription, whereas the phosphorylation of serine 133 (phospho‐Ser133) in its kinase‐inducible domain (KID) is its main transactivating form. Phospho‐Ser133 plays a role in CREB to bind the KIX domain of the coactivators CBP and p300 (CBP/p300) 50. Vecsey et al25 demonstrated that enhancement of hippocampus‐dependent memory and synaptic plasticity by HDAC inhibitors was relied on the binding of CREB and CREB‐binding protein (CBP), which induced robust activation of gene transcription afterwards.…”
Section: Discussionmentioning
confidence: 99%